أقسام الإدارج في المعجم الأوسط (دراسة تطبيقية ونموذجية) - Abdul Samee Jessar; Prof. Dr. Fateh-Ur-Rehman Qureshi (البصيرة, 2023)
Idraj(ادراج)   is a specific term in the field of Hadith which means Text Inclusion. It has different kinds with varying effects (Ilal) on Hadith's understanding, and it may also have effects on Hadith's authenticity. This research explains some types of Inclusion and authenticity of Hadith's chains. The topic of this research is "Kinds of inclusive (Idraj) text in “Al-Mujamul Awsat". Inclusive text has many types.  Some of them are: scholar’s words, explanations or understanding Included into Hadith, Inclusion Hadith al Muquf into Hadith Al Marfh, Inclusion words that originally are not from Hadith, and lastly, Inclusion of Idraj Hadith into another Hadith. These kinds may or may not affect authenticity of Hadith and their understanding. The research is practical in its nature. We have taken some Hadiths from “Al-Mujamul Awsat” that are relative to the topic Idraj, and taken all chains of relative Hadith and compared their authenticity through textual comparison.  Takhreej of such types of hadith has also been done. After that, its Illat have been studied too. Researcher’s opinion follows at the end of every Hadith.